已知a+b+c=0,求证:a^3+a^2c—abc+b^3=0
1个回答
题目结论有误
a^3+a^2c—abc+b^3
=a^2 (a+c) -abc+b^3
=-a^2 b+ab(a+b)+b^3
=ab^2+b^3
=-b^2 c
相关问题
已知a+b+c=0,求证:a^3+a^2c+b^2c-abc+b^3=0.
已知a+b+c=0求证:a3+b3=-a2c-b2c+abc
已知:a>0,b>0,c>0,求证:a3+b3+c3>=3abc
已知a+b+c=0求证a3+a2c+b2c-abc+b3=0谢谢帮忙啊
已知:a>b>c>0,求证:(a^a)(b^b)(c^c)>(abc)^((a+b+c)/3)
已知a+b+c=0,求证a³+b³+c³=3abc过程解释
已知,a,b,c均大于0,求证,a^3+b^3+c^3>=3abc
已知a-3c=0,b/c=2,abc≠0,求(a+2b+3c)/(3a+2b+c).
已知a>0,b>0,c>0,求证:(1)(a+b)(b+c)(c+a)>=8abc;(2)(a/b)+(b/c)(c/a
已知,a,b,c>0,求证:a3+b3+c3≥13(a2+b2+c2)(a+b+c).